International seminar on the communication and the durable development in agriculture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
International Seminar on Communication and Sustainable Development in Agriculture. Du 7 au 9 janvier 2003, Baranas Hindu University, Varanasi, Inde / From 7 to 9 January 2003, Baranas Hindu University, Varanasi, India.